THE AWARENESS OF HOUSEWIVES IN CONSUMING HALAL FOOD IN MURUY VILLAGE PANDEGLANG DISTRICT - Elly Nurlia (International Journal Mathla’ul Anwar of Halal Issues, 2022)
Indonesia is a country with the largest Muslim population, thus food quality needs to be considered in accordance with existing Islamic law. This study aims to determine how the level of awareness of housewives in Muruy village, Pandeglang Regency in consuming halal food and how the behavior of housewives in choosing halal food. This research method used qualitative in the form of a case study. The data were collected through in-depth interviews with housewives who are active in diversity activities in Muruy Village, Pandeglang Regency. The results showed that the level of awareness of housewives in consuming halal food is quite good, but there is still a lack of attention to the awareness of the ingredients in food products. In addition, several behaviors were found that motivate housewives in choosing halal food products.